Analysis Of Competitive Strategy For Grocery Stalls (Study On Herianto’s Grocery Stalls, Camba-Camba Village, Batang District, Jeneponto Regency) - Hendriani; Muhammad Darwis; Sulmiah; Aris Baharuddin; Jamaluddin (Fakultas Ilmu Sosial dan Hukum, 2026)
This study aims to determine how the competitive strategy of Herianto grocery stalls and inhibiting and supporting factors in Herianto grocery stalls, Camba-camba village, Batang district, Jeneponto regency. This type of research is descriptive qualitative research. Data collection techniques in this study through observation, interview, and documentation methods. Data analysis techniques in this study use data condensation, data presentation and conclusions. The results of this study show that in order for Herianto grocery stalls to remain competitive in the same industry, Herianto grocery stalls can choose several strategies that are in accordance with the internal and external conditions of grocery stalls. The strategy that can be used at Herianto's grocery stall is to use the WO strategy where the purpose of the WO strategy is to improve internal weaknesses by taking advantage of external opportunities. The strategy is obtained from the results of SWOT analysis and by looking at business competition factors, namely, the threat of substitute poduk, the threat of competitors, the threat of new competitors, the bargaining power of suppliers, the bargaining power of consumers. The inhibiting factor is the lack of business capital so that consumers still cannot buy wholesale and the stall building is still narrow. The supporting factors are the completeness of goods, ease of shopping by implementing a 2-week payment system and implementing a delivery system.